Comprehensive performance analyses and optimization of the irreversible thermodynamic cycle engines (TCE) under maximum power (MP) and maximum power density (MPD) conditions. (25th June 2015) - Gonca, Guven; Sahin, Bahri; Ust, Yasin; Parlak, Adnan
Abstract: This paper presents comprehensive performance analyses and comparisons for air-standard irreversible thermodynamic cycle engines (TCE) based on the power output, power density, thermal efficiency, maximum dimensionless power output (MP), maximum dimensionless power density (MPD) and maximum thermal efficiency (MEF) criteria. Internal irreversibility of the cycles occurred during the irreversible-adiabatic processes is considered by using isentropic efficiencies of compression and expansion processes. The performances of the cycles are obtained by using engine design parameters such as isentropic temperature ratio of the compression process, pressure ratio, stroke ratio, cut-off ratio, Miller cycle ratio, exhaust temperature ratio, cycle temperature ratio and cycle pressure ratio. The effects of engine design parameters on the maximum and optimal performances are investigated. Highlights: Performance analyses are conducted for irreversible thermodynamic cycle engines. Comprehensive computations are performed. Maximum and optimum performances of the engines are shown. The effects of design parameters on performance and power density are examined. The results obtained may be guidelines to the engine designers.